Income underreporting based on income expenditure gaps: Survey vs tax records - Alari Paulus (University of Essex, Institute for Social and Economic Research (ISER), 2015)
We estimate the extent of income underreporting among working households, using data from an income survey linked with individual tax records for Estonia. Income underreporting is inferred from consumption propensities, following and extending the method by Pissarides andWeber (1989). Our dataset allows us to assess the validity of the key assumption in related studies that survey income corresponds to income reported to the tax authority. Our results show large underreporting of earnings by the self-employed and also substantial underreporting of earnings by private sector employees on the basis of register income, while a much smaller scale of non-compliance is detected for self-employed and no underreporting for private employees using survey incomes. This suggests that previous studies applying this methodology to survey data have underestimated the extent of non-compliance.
Keywords: H26; H31; 330; tax compliance; tax reports; income survey; expenditure; Estonia